Vers une révision du processus et du cadre d'élaboration de la décision administrative au Québec - Longtin, Marie-José; Bouchard, Mario (Les Cahiers de droit, 1981)
In this study, the authors examine various models for reviewing the system and procedural framework of administrative action in Québec. Firstly, they explore the solutions previously advanced as far as Québec is concerned, then those that have been adopted in other jurisdictions. Next, after identifying the principle decision-making agents of the administration, they enumerate the other factors to be considered in devising a model system, such as the assigned powers of the decision-makers, their procedure, the rules controlling their decision-making, and the establishement by the decision-makers of norms governing the exercise of their discretionary powers. These parameters having been determined the authors go on to evaluate, from various aspects, those solutions that have already been proposed and also others which offer themselves for consideration. In that regard, after discussing the classification of administrative bodies, they analyse the merits of a single or dual jurisdictional authority from the structural and constitutional perspective ; they pause to examine the very notion of administrative authority before going on to deal with the issue of an overall control of administrative bodies, such control being exercised by means of an Administrative Council. Then, after discussing the power given to an administrative body or agency to review its own decisions, they analyse the controversial issue of administrative procedure ant the codification of those rules, and go on to propose, as a possible solution, a flexible codification that is restrictive in part yet adaptable to the individual circumstances of the bodies concerned. In concluding that the existing patchwork of administrative decisionmaking must be satisfactorily resolved, and before indicating what corrective action should be studied, they attempt to identify the questions that have to be answered before undertaking review of the system and procedural framework of administrative action, the need for which review having been seen as imperative right from the outset.